Preparation, in vitro evaluation and molecular modelling of pyridinium-quinolinium/isoquinolinium non-symmetrical bisquaternary cholinesterase inhibitors - Komloova, Marketa; Horova, Anna; Hrabinova, Martina; Jun, Daniel; Dolezal, Martin; Vinsova, Jarmila; Kuca, Kamil; Musilek, Kamil (Bioorganic & medicinal chemistry letters, 2013)
Two series of non-symmetrical bisquaternary pyridinium-quinolinium and pyridinium-isoquinolinium compounds were prepared as molecules potentially applicable in myasthenia gravis treatment. Their inhibitory ability towards human recombinant acetylcholinesterase and human plasmatic butyrylcholinesterase was determined and the results were compared to the known effective inhibitors such as ambenonium dichloride, edrophonium bromide and experimental compound BW284C51. Two compounds, 1-(10-(pyridinium-1-yl)decyl)quinolinium dibromide and 1-(12-(pyridinium-1-yl)dodecyl)quinolinium dibromide, showed very promising affinity for acetylcholinesterase with their IC50 values reaching nM inhibition of acetylcholinesterase. These most active compounds also showed satisfactory selectivity towards acetylcholinesterase and they seem to be very promising as leading structures for further modifications and optimization. Two of the most promising compounds were examined in the molecular modelling study in order to find the possible interactions between the ligand and tested enzyme.
Keywords: Protein Binding; Cholinesterase Inhibitors; Recombinant Proteins; Cholinesterase; Enzyme Activation; vazebná místa; Protein Structure, Tertiary; Benzenaminium, 4,4'-(3-oxo-1,5-pentanediyl)bis(N,N-dimethyl-N-2-propenyl-), Dibromide; Structure-Activity Relationship; terciární struktura proteinů; chinolinové sloučeniny; Inhibitor; Myasthenia gravis; acetylcholinesterasa; Pyridinium Compounds; molekulární modely; vztahy mezi strukturou a aktivitou; Molecular modelling; Quinolinium Compounds; rekombinantní proteiny; Models, Molecular; vazba proteinů; Binding Sites; pyridinové sloučeniny; lidé; Humans; Butyrylcholinesterase; benzenaminium, 4,4'-(3-oxo-1,5-pentandiyl)bis(N,N-dimethyl-N-2-propenyl-), dibromid; In vitro; aktivace enzymů; butyrylcholinesterasa; Acetylcholinesterase; cholinesterasové inhibitory